Family characteristics in adolescents with overweight or obesity: a network analysis - Huang, Lidong; Zhao, Kang; Zhu, Hanfei; Li, Xiaonan; Yang, Yiqing; Hou, Caiyun; Zhu, Shuqin; Xu, Qin (Frontiers in Pediatrics, 2023)
Background Rates of overweight and obesity continue to grow in adolescents. Overweight and obesity in adolescence are associated with numerous immediate and long-term adverse health conditions. Throughout adolescence, parents and the family have an important and central influence on adolescents' health and lifestyle. The home environment may be a major factor in shaping children's weight. However, our current understanding of the interplay between family-related variables in adolescents with overweight or obesity is limited and fragmented. This study aimed to assess the relationship between family-related variables in adolescents who are overweight or obese using network analysis and inform future health promotion for family-based intervention.Methods Participants(n=488) were recruited from middle schools in Nanjing from October 2022 to March 2023. Participants, together with their parents, completed a questionnaire at school about the family food environment, family size, family APGAR index, family physical activity facilities, parental mental health, rearing behavior, parental weight status, drinking history, marital satisfaction, and sociodemographic characteristics.The network split into three distinct communities of items. Network analysis showed that parental mental health and paternal rearing styles-rejection were the most central nodes in the network. In contrast, maternal weight status was the most peripheral and least connected nodes.Family-related variables constituted a connected network in adolescents with overweight or obesity. The pattern of network node connections supports that interventions could prioritize targeting changing parental mental health and paternal rearing styles in adolescents with overweight or obesity.